INCREASING CENTRIFUGAL PUMP PERFORMANCE - S. V. Mikhaylova; I. A. Pogrebnaya (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives Investigate the prospect of improving the quality of centrifugal pumps in oil production.Method The method is based on energy-efficient installations for high-yield wells - the steps of the Borets-Weatherford installations and the Borets PC stages.Result The main hydraulic characteristics of electric centrifugal pumps with the use of energy-efficient stages with the recommended feed range have been developed. The dependence of the maximum efficiency on the applied steps of the above installations has been determined. A comparative analysis of energy-efficient and commercially available installation of electric centrifugal pumps is given. The dependence of the parameters of the installation steps on the flow, head, number of stages, nominal speed and efficiency of the pump is given.Conclusion When using submersible pumps of the 10ECNM type in oil fields, increased reliability and durability were noted, in contrast to the use of submersible ECNM-type pumps. With the help of energy efficiency programs for oil production, implemented by oil companies, by ensuring more efficient operation of pumping equipment, power consumption has been reduced. The adoption of promising solutions to improve the energy efficiency of ESP systems is a priority. The use of energy-efficient ESP systems for the operation of high-rate and low-rate wells allows to ensure maximum efficiency of the submersible equipment and reduce the specific electricity consumption. In a comparative analysis of the characteristics of pumps with a daily flow of 400 m3, the use of an energyefficient installation ESP 400–2200 with FEA provides three times lower energy costs. A comparative analysis of the energy efficiency of the presented pumps shows that the use of energy-efficient installations of electric centrifugal pumps produced by PC Borets LLC will reduce energy costs by an average of 30%.